Increasing The Added Value Of Marine Products: Fish Processing Diversification Training For Fishermen Groups In Tanjung Riau Fishing Village - Rosie Oktavia Puspita Rini; Saputra, Eryd; Arif Gunawan, Agung (PUSLITABMAS-Politeknik Pariwisata Batamc, 2025)
This community service activity aims to increase the added value of marine products through training on processed fish diversification for fishermen groups in Tanjung Riau Fishing Village. This program is a collaboration between the Culinary Management Study Program of the Batam Tourism Polytechnic and the local community, with the main target of small-scale capture fishermen, fishermen's families, young fishermen, and micro-business groups based on marine products. The main problems faced by coastal communities, namely the low selling value of fresh fish and marine product waste that has not been optimally utilized, are overcome through educational and applicative approaches. The activity methods include field identification, initial socialization, practical training, utilization of marine product waste, and post-training evaluation. The training is carried out directly with a learning by doing approach, covering processing techniques for products with economic value such as Prawn Bisque and Dry Prawn Powder. The training material also emphasized the importance of hygiene standards, food safety, and the use of shrimp shell waste as part of the circular economy principles. The results of the activity showed an increase in the knowledge and skills of participants in processing seafood into processed products with high selling value and awareness of environmentally friendly waste management. This activity also contributes to opening new business opportunities and strengthening the entrepreneurial spirit of coastal communities. With an integrated approach between education, technical training, and empowerment, this activity is expected to have a sustainable impact on economic, social, and environmental aspects in coastal areas.